Curriculum Research and Development in the Humanities and Social Studies - Schools Council, London (England).; Schools Council, London (England). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This bulletin offers information on nineteen Schools Council research and development projects contributing useful ideas and resources to elementary and secondary educators. These projects advocate an inter-disciplinary approach using team-teaching methods. Many projects overlap in themes, ideas and teaching strategies. Although the projects are concerned with a similar range of topics or issues, project-developed materials are relevant to programs in geography, liberal studies, humanities, history, moral education, social studies, religious education, environmental studies, ethnic studies, and to programs for early leaving pupils. Strategies vary from producing research reports, teaching guides, and teaching materials to combining all of these. The first part of the paper offers a generalized description of the projects. The projects are listed in the second part, including project titles, comprehensive annotations, materials, grade designations, and director's names and addresses. A selected Schools Council bibliography of examinations bulletins, working papers, pamphlets, articles, and other publications appears in the last part of the bulletin. (SJM)
Educational level discussed: Elementary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Development; Curriculum Research; Elementary Education; Environmental Education; Geography; History; Humanities; Interdisciplinary Approach; Projects; Secondary Education; Social Sciences; Social Studies; Team Teaching; Schools Council (England)